Copywriting successful writing for design, advertising and marketing - Shaw, Mark (London, United Kingdom Laurence King Publishing Ltd, 2015)
"Creating effective copywriting is of vital importance in today's design and communication industries. Well-targeted copy and a strong brand voice are essential if you want to stand out from the competition. Copywriting shows how to write for all formats and contexts, from catalogs and products to advertising and websites. It explores the challenges of commercial writing, providing the tools to become a confident and versatile copywriter. Leading industry talents from both the US and UK are interviewed, major campaigns covering all areas of the industry are illustrated in color and examined in depth, and exercises and tips aid in developing writing, editing, and presentation skills. Revealing the secrets of this rapidly expanding profession, Copywriting provides the skills and techniques that will help you to thrive in the world of creative commercial writing." -- Goodreads.com
Keywords: Advertising copy; Communication in marketing; Branding (Marketing); Advertising, Magazine; Conceptual art; Language arts; Rhetoric -- Study and teaching